2022
DOI: 10.3389/fpain.2022.840328
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Diffusion Tensor Tractography and Clinical Applications in Pain

Abstract: The brainstem is one of the most vulnerable brain structures in many neurological conditions, such as pain, sleep problems, autonomic dysfunctions, and neurodegenerative disorders. Diffusion tensor imaging and tractography provide structural details and quantitative measures of brainstem fiber pathways. Until recently, diffusion tensor tractographic studies have mainly focused on whole-brain MRI acquisition. Due to the brainstem's spatial localization, size, and tissue characteristics, and limits of imaging te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated that DTI changes in WM regions are associated with pain, although they exhibit inter-study variability. 62 The current study found a multitude of overlaps with regions implicated in pain perception. The anterior corona radiata (ACR) in the BMS group showed lower MD and RD and higher ICVF.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies demonstrated that DTI changes in WM regions are associated with pain, although they exhibit inter-study variability. 62 The current study found a multitude of overlaps with regions implicated in pain perception. The anterior corona radiata (ACR) in the BMS group showed lower MD and RD and higher ICVF.…”
Section: Discussionmentioning
confidence: 56%
“…In neurological conditions, reduced FA and increased ADC or RD are attributed to demyelination, loss of axons, or an interrupted connection. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%